'Buildings as Power Stations': An Energy Simulation Tool for Housing. (2015) - Coma, Ester; Jones, Phil
Abstract: The concept of 'Buildings as Power Stations' (BAPS) represents a major shift in the way that electricity is generated, stored and used. Buildings are no longer simply consumers of electricity, but active players in the electric power system. Reducing energy demand to 'PassivHaus' levels of performance and the full integration of photovoltaic modules and wind turbines with buildings is itself a challenge to architects and house builders. Combining these with the sizing of the batteries for electrical storage through a 'systems' approach, optimizing performance and cost across reduced energy demand, renewable supply and storage, needs a suitable 'user-friendly' modeling framework, which is currently not generally available to designers. The new BAPS tool presented in this paper assesses if a building has the potential to become a 'Power Station' by analyzing the energy generated from building-integrated renewables (including, solar and wind), the effect of using electrical energy storage systems and the impact of introducing demand reduction technologies. The BAPS tool enables an architect, via an easy to understand user interface, to assess the potential for renewable energies and battery storage and provides guidance on the selection of the battery system for a range of residential applications. The paper describes how the tool has been used in the design of the prototype 'near zero' carbon SOLCER House, currently under construction in South Wales, UK. The tool has been used to evaluate the building energy system, including the sizing of solar PV panels and the li-ion battery storage, in the context of the buildings reduced demand for electricity, through the use of LED lighting and high efficiency appliances. The optimum mix of renewable energy and grid based energy supply is presented for the SOLCER House.